Logical Semantics of Speech and Transition to an Intersubjective World in Husserlian Phenomenology - alireza Faraji (حکمت و فلسفه, 2021)
Husserl in his method of phenomenology casts a new light on the discussion of experience through a new definition of cognition and avoids the error of preceding philosophers, classic empiricists, in particular; thus the cognition is no longer based on the immediate experiences of the world but it is based on intentional experience which relies upon immediate intuition of objects. The result of this perception is a live experience. Therefore, for Husserl, knowing the world around us is based on the lived which is based on the intentionality of consciousness. For Husserl, talking about this intentional world happens through ideal meanings and this group of meanings rests around the axis of a transcendental ego which is the center of intentional actions and moods. Therefore, the analysis of the speech act of this “ego” is done through semantics and based on transcendental logic and it is separated from syntactic theory. Husserl makes this new change to move the transcendental subject into the intersubjective world. In the present research, the objective is to analyze the effect of logical semantics on speech and transition to the intersubjective world.